(untitled) (Intent Research Scientific Journal, 2023)
Before storing the seeds, the moisture content should be reduced to the optimum level. There are several methods of drying seeds, the most common of which are the use of drying chambers and the use of absorbent equipment. The methods used in drying are selected based on the climatic conditions of the region, the composition and size of the stored plant species, the available material and technical base, and also the financial conditions. However, it should be noted that no matter what method of drying is used in the gene bank, the eternal preservation of the seed is not guaranteed. Drying (weakening) seeds to a critical (limiting) level makes it possible to store this seed up to the maximum allowed period. If the critical moisture level is not followed during the seed drying stage, then the storage capacity of the seed will decrease. In light of the above, all operating genebanks are mandated to dry seeds to the critical moisture point before placing them in refrigerated or frozen storage. By applying different combinations of temperature and moisture concentration during the drying process, seed drying can be accelerated or slowed down. It should also be taken into account that if the seeds are dried at low temperatures, then the physiological aging process of the mature plasma slows down, but the seeds dried at high temperatures require relatively less time.